High serum CXCL10 in Rickettsia conorii infection is endothelial cell mediated subsequent to whole blood activation. (July 2016) - Otterdal, Kari; Portillo, Aránzazu; Astrup, Elisabeth; Ludviksen, Judith; Davì, Giovanni; Holm, Sverre; Santilli, Francesca; Vitale, Giustina; Raoult, Didier; Olano, Juan P.; Schjalm, Camilla; Halvorsen, Bente; et al.
Highlights: High levels of CXCL10 were observed in patients with R. conorii infection. The CXCL10 levels decreased markedly after recovery of the patients. R. conorii induced a marked CXCL10 increase in a blood/endothelial co-culture model. Plasma from R. conorii -exposed blood induced marked CXCL10 release from endothelium. Abstract: Background: The pathophysiological hallmark of Rickettsia conorii ( R. conorii ) infection comprises infection of endothelial cells with perivascular infiltration of T-cells and macrophages. Although interferon (IFN)-γ-induced protein 10 (IP-10)/CXCL10 is induced during vascular inflammation, data on CXCL10 in R. conorii infection is scarce. Methods: Serum CXCL10 was analyzed in two cohorts of southern European patients with R. conorii infection using multiplex cytokine assays. The mechanism of R. conorii -induced CXCL10 release was examined ex vivo using human whole blood interacting with endothelial cells. Results: (i) At admission, R. conorii infected patients had excessively increased CXCL10 levels, similar in the Italian (n = 32, ∼56-fold increase vs controls) and the Spanish cohort (n = 38, ∼68-fold increase vs controls), followed by a marked decrease after recovery. The massive CXCL10 increase was selective since it was not accompanied with similar changes in other cytokines. (ii) Heat-inactivated R. conorii induced a marked CXCL10 increase when whole blood and endothelial cells were co-cultured. Even plasma obtained from R. conorii -exposed whole blood induced a marked CXCL10 release from endothelial cells, comparable to the levels found in serum of R. conorii -infected patients. Bacteria alone did not induce CXCL10 production in endothelial cells, macrophages or smooth muscle cells. Conclusions: We show a massive and selective serum CXCL10 response in R. conorii -infected patients, likely reflecting release from infected endothelial cells characterized by infiltrating T cells and monocytes. The CXCL10 response could contribute to T-cell infiltration within the infected organ, but the pathologic consequences of CXCL10 in clinical R. conorii infection remain to be defined.